Exploring Challenges Faced by Rural Zimbabwean School-Going Single Mothers in Nurturing Children: A Literature Perspective - Chikuvadze, Pinias; Magutsa, Lydia K.; Musengi, Judith; Gonzo, Getrude (Mediterranean Journal of Social Sciences, 2021)
In sub-Saharan African countries, school-going single mothers are a rapidly growing new form of family. However, this pervasive phenomenon and its influence on child development have caught miniature thought. It is in this context that this paper sought to gain insights from a literature perspective on challenges confronted by rural Zimbabwean school-going single mothers in child nurturing. This is a documentary review of information considered relevant to the issue under investigation. In this context, the literature method was used in generating, data from purposively sampled sources. Against this background, the analysis revealed that school-going single mothers encounter numerous challenges, such as the difficulty to maintain discipline and authority in their ‘new’ family setting, social ostracism through school-going single mothers, and their children's experience of adverse stances in social, emotional and economic obstacles. Thus, single mothers in these rural societies take on all the chores, child upkeep and in most cases are susceptible to social separation, which forms a situation, which does not bring up children’s social and cognitive development. In this context, it can therefore be concluded that these detected challenges influence how school-going single mothers in the rural Zimbabwe context nurture their children. It is against this background that we recommend that school-going single mothers are encouraged to find means of exercising positive parenting that ensures that their children are well-groomed and provided for. Received: 11 February 2021 / Accepted: 20 April 2021 / Published: 17 May 2021